Enhancing Environmental Performance: A Method for Identifying and Prioritizing Key Environmental Issues in Industry - Dellise Marie; Jonathan Villot; Rodolphe Gaucher; Anne Amardeil; Valérie Laforest (Clean Technologies)
BAT-based regulations necessitate defining key environmental issues (KEIs) to focus data collection and discussions on the main topics when establishing best available techniques (BATs) at the sector level. However, Article 14 of the Industrial Emissions Directive (IED) suggests that some significant environmental issues may not be covered by BAT conclusions but still require the implementation of BATs at the local level, even in the absence of defined sectoral BAT references. The IED, along with the associated Commission Implementing Decisions and guides, does not offer guidelines for selecting KEIs at the local level, whether by the competent authority or the operator. To ensure full compliance with the IED by installations under its scope, this paper proposes a methodology for determining KEIs locally. Based on the environmental aspects of the installation, the sensitivity of the environment, and the levels of emissions or consumption, this methodology has been tested on a case study at the plant level to demonstrate its effectiveness. The paper then discusses the contributions and limitations of the methodology and suggests areas for future research. The proposed methodology was tested at the factory level, where it effectively identified and prioritized key environmental issues (KEIs) by focusing on site-specific environmental aspects not covered by sectoral BAT conclusions. The results suggested improved alignment with local environmental challenges, indicating the methodology’s effectiveness in capturing key issues that may require immediate action under Article 14 of the IED. This approach provides a practical framework for prioritizing environmental impacts based on local context and regulatory requirements.